2017
DOI: 10.3926/jiem.2020
|View full text |Cite
|
Sign up to set email alerts
|

Critical successful factors for innovation in vietnamese firms

Abstract: Abstract:Purpose: Innovation is considered as a core element of sustainable competitive advantage in the rapidly changing environment. However, in Vietnam, researches on innovation are very rare, which are mostly general reports without underlying analyses of innovation in firms, especially determinants for innovation. Therefore, this paper focuses on analyzing critical successful factors for innovation in Vietnamese firms. Originality/value: This study makes a contribution for both academics and practitioners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…This is especially so in practices such as recruitment and training which are closely linked to organizational innovation. Empirical research has edalso confirmed that E-HRM positively affected knowledge creation (Collins & Smith, 2006) as well as learning and innovation (Nam et al, 2017). Therefore, the present study has proposed that;…”
Section: Electronic Human Resource Management (E-hrm) Andsupporting
confidence: 52%
See 1 more Smart Citation
“…This is especially so in practices such as recruitment and training which are closely linked to organizational innovation. Empirical research has edalso confirmed that E-HRM positively affected knowledge creation (Collins & Smith, 2006) as well as learning and innovation (Nam et al, 2017). Therefore, the present study has proposed that;…”
Section: Electronic Human Resource Management (E-hrm) Andsupporting
confidence: 52%
“…A knowledge-oriented leadership style will assist in creating the required knowledge and then processes whatever general knowledge into specific information that can play a critical role to further the innovation process. The significance of knowledge-oriented leadership with respect to innovation was its emphasis on the role of systems and to always keep culture and structure in mind (Nam et al, 2017). Knowledgeable leaders have a vital responsibility to execute a positive and complex change in order to achieve the company's goals.…”
Section: Knowledge Oriented Leadership and Organisational Innovationmentioning
confidence: 99%
“…Additionally, the question of enhancing higher building capabilities activities within an organization has yet to be effectively resolved [9]. This argument is also shared that attention should be paid to improving the staff level, especially managers, and encouraging employees to contribute to the innovation [10].…”
Section: The Actual Situation Of Technology Transfer At the Enterpris...mentioning
confidence: 99%
“…A positive relationship has been shown between the product and process innovation in an organization (Escribá-Carda, Canet-Giner & Balbastre-Benavent, 2014). To innovate and promote creativity, the organizations have to pay full attention by providing rewards to the employees that adopt innovation (Nam, Tuan, & Van, 2017). Organizations need to focus on E-HRM, spend more to digitize and to achieve a dynamic business environment for Industry 4.0.…”
Section: Mediating Role Of Organization Innovationmentioning
confidence: 99%